Night Work Culture in Professional and Sharia Perspectives - Mahmudulhassan; Muhammad Abuzar; Andri Nirwana (Walidem Institute and Publishing, 2024)
This study aims to investigate work culture and sharia views on night work, focusing on responsibility, ethics, and its impact. This research method uses a qualitative approach by conducting a literature review and analysis of relevant primary and secondary sources. The results show that modern work culture often encourages individuals to work at night, especially in the service, health, and hospitality industries. Nevertheless, the Sharia view emphasizes the importance of balance between work and worship, as well as maintaining physical and mental health. In this context, working nights can pose moral and social challenges that need to be carefully considered. The novelty of this research lies in merging the perspective of modern work culture with the view of sharia, which is rarely explored thoroughly. The results of this analysis provide a deeper understanding of individual responsibilities in undergoing night work, as well as provide ethical guidance relevant to the Islamic context. In conclusion, this research can provide valuable insights for individuals, organizations, and communities in understanding the implications of night work from the point of view of work culture and sharia